TINJAUAN TENTANG PEMBINAAN OLAHRAGA BELADIRI PENCAK SILAT DI KABUPATEN KAMPAR - Anita Dewi Rahayu; Ramadi Ramadi; Rusmanto Rusmanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this study is to find out how the performance coaching system, the quality of the coach, the athlete recruitment system, infrastructure, the financial system of athletes in the Pencak Silat sport in Kampar Regency. The type of research is descriptive qualitative in using the questionnaire and question and answer method then the questionnaire is distributed to the object of research after which the researcher does the coding of accurate data coding. This research was conducted at IPSI Kampar Regency Jl. Rahman Saleh, Bangkinang Village, Bangkinang District, Kampar Regency, Kampar Province. This research was conducted in February 2022-June 2022 at IFSI Kampar Regency. In this study a sample of 18 people. Data analysis is the process of systematically searching and compiling data obtained from interviews, field notes, and documentation, by organizing the data into categories, describing them into units, arranging them into patterns, choosing which ones are important and will be studied, and draw conclusions so that they can be understood by themselves or others. Based on the results of research and discussion, it can be concluded that the following conclusions can be drawn: Recommendations from athletes in good category with a percentage of 55%, while the results of the questionnaire from coaches are in the good category with a percentage of 73% and the results of questionnaires from administrators with a percentage of 32% in sufficient category good. The results showed that the coaches in coaching the sport of Pencak Silat in Kampar Regency already had sufficient technical mastery and experience. Of the 2 existing coaches and 1 manager, both have good quality and experience. Based on the results of this study indicate that the elements of coaching are fulfilled and there are supporting factors that support the success of a coaching system.Key Words: Overview of Development, Martial Arts, Pencak Silat.